A case report of retroperitoneal leiomyosarcoma originating from the right ovarian vein and invading the right renal vein and inferior vena cava - Chengbin Lu; Leyu Zhang; Benmo Xu; Tianyu Li; Die Fan; Changyang Li; Yuanlong Shi; Xin Li; Bin Zhao (Journal of International Medical Research)
A woman in her early 50s was admitted to our hospital with a right retroperitoneal tumor that had been detected >1 year ago. Imaging studies revealed a mass in the right middle and lower retroperitoneum, which involved the upper portion of the right fallopian tube and caused dilated hydronephrosis of the right renal pelvis and calyces. Initial diagnosis suggested benign intraventricular smooth muscle neoplasia. She underwent surgical resection of the right retroperitoneal tumor, along with thrombectomy of the right renal vein and inferior vena cava, as well as artificial revascularization of the right renal vein. Postoperative pathology confirmed retroperitoneal smooth muscle sarcoma. She received postoperative chemotherapy with ifosfamide and doxorubicin as well as anticoagulation therapy with rivaroxaban. One year later, follow-up imaging revealed multiple nodules in the right middle and lower abdomen, a blurred nodule in the tail of the pancreas, and a dilated pancreatic duct in the distal pancreas, raising suspicion of metastasis.